Five‐to‐Seven Carbon Glycols Severely Impair Bioenergetics and Metabolism of Aggressive Lung Cancer Cells. Issue 9 (16th August 2022) - Stefanello, Sílvio Terra; Mizdal, Caren Rigon; Azzam, Ihab; Döhlinger, Lilly; Oeckinghaus, Andrea; Shahin, Victor
Abstract : Lung cancer is the leading cause of cancer deaths. Nonsmall cell lung cancer (NSCLC) accounts for the vast majority of the histological subtypes and at advanced stage exhibits extremely low survival rate. Certain compounds, such as glycols, inhibit migration and decreased viability of the highly metastatic NSCLC cells A549_3R has been recently shown. The glycols‐induced effects are associated with a parallel reduction of ATP production, detected in A549_3R spheroids embedded in 3D desmoplastic‐like extracellular matrix, following overnight treatment. Herein, selected glycols are tested for their ability to acutely compromise bioenergetics, metabolism, and viability of A549_3R cells. Therefore, 1, 5‐pentanediol (1, 5‐PD), 1, 6‐hexanediol (1, 6‐HD), and 1, 7‐heptanediol (1, 7‐Hept) turn out to be the most effective. They interfere with key enzymes in glycolysis and elicit most or all of the following responses: acute collapse of the critical mitochondrial membrane potential, substantial reduction of ATP, pyruvate and L‐lactate levels, and massive increase in reactive oxygen species production. Moreover, computational docking analysis reveals that the glycols bind to the substrate‐binding residues of lactate dehydrogenase A, which catalyzes the interconversion of pyruvate and lactate and is upregulated in aggressive tumors. Hence, the effective glycols may be promising anticancer compounds, or lead substances, for localized and intratumoral applications. Abstract : The proposed mechanism of the action of 1, 5‐PD, 1, 6‐HD, and 1, 7‐Hept that negatively impacts the metabolism and bioenergetics of aggressive lung cancer cells is discussed.